1998
DOI: 10.1111/j.1398-9995.1998.tb03843.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensory hyperreactivity – a possible mechanism underlying cough and asthma‐like symptoms

Abstract: The capsaicin provocation test may be a valuable method for showing not only a greater cough sensitivity, but also asthma-like symptoms. The pathophysiology underlying the symptoms may be related to increased sensitivity of free, overactive nerve endings in the respiratory mucosa. Therefore, we suggest that this overreaction in the lower airways be called "sensory hyperreactivity".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
138
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(145 citation statements)
references
References 11 publications
7
138
0
Order By: Relevance
“…The tidal breathing method of capsaicin challenge, used in the present study, was developed for SHR and has been modified with time and has shown good reproducibility [5,9,24,40]. The testing of cough sensitivity with capsaicin inhalation is otherwise often performed with a "single-breath" technique using increasing concentrations of capsaicin until the individual coughs, for example, two or five times (C2 or C5), which has shown a good reproducibility [41,42].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The tidal breathing method of capsaicin challenge, used in the present study, was developed for SHR and has been modified with time and has shown good reproducibility [5,9,24,40]. The testing of cough sensitivity with capsaicin inhalation is otherwise often performed with a "single-breath" technique using increasing concentrations of capsaicin until the individual coughs, for example, two or five times (C2 or C5), which has shown a good reproducibility [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…The single-breath technique was more dependent on a standardized inhalation technique compared to the fixed time and concentration technique [44]. One potential problem with using the "single-breath" technique is that patients with SHR have an easily evoked cough reflex, and even inhalation of saline can induce coughing [9,40]. The occurrence of a tachyphylaxis problem after performing the test with the single-breath technique speaks in favour of the tidal breathing technique used in this study, which has also been discussed by other authors [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Millqvist et al first proposed the term airway sensory hyperreactivity (SHR) to define a syndrome of self reported odour intolerance combined with heightened sensitivity to inhaled capsaicin [16]. An accurate estimate of the prevalence of SHR in the general population is…”
Section: How Common Is Airway Sensory Hyperreactivity (Shr)?mentioning
confidence: 99%
“…The sense of air hunger appears to arise from an increased brain stem 'drive' to breathe (35,36,52,53). Even patients with normal lung function and without signs of hypercapnia and hypoxia may suffer from air hunger (51,(54)(55)(56)(57). Thus, activation of airway sensory nerves may lead to dyspnea, which need not necessarily be dependent on bronchial constriction (51).…”
Section: Dyspneamentioning
confidence: 99%